Small wetlands are critical for safeguarding rare and threatened plant species. Issue 2 (30th October 2014) - Richardson, Sarah J.; Clayton, Richard; Rance, Brian D.; Broadbent, Hazel; McGlone, Matt S.; Wilmshurst, Janet M.; Middleton, Beth
Abstract Question Rare and threatened species are a common focus of natural area protection, but selecting sites to protect them must be balanced against other conservation objectives. Using a series of wetlands as a case study, we ask: (i) will protecting sites based on species rarity capture all critical community types; (ii) do rare plant species occur in rare environments; and (iii) will safeguarding large wetlands protect taxonomic and functional richness of rare and threatened species? Location Southern New Zealand. Methods We used lists of vascular plant species from 118 wetlands (66 fens, 35 bogs and 17 marshes). The resulting species lists included 29 rare and threatened species. Nine functional attributes of the rare and threatened species were compiled. Species assemblages were ordinated using non‐metric multidimensional scaling. Permutational multivariate ANOVA tested for a difference in assemblages between wetlands with or without rare and threatened species. Wetlands were classified according to a rare environment scheme. SLOSS (single‐large‐or‐several‐small) accumulation curves determined whether species and functional richness of rare and threatened species were best captured by groups of small or large wetlands. Results Wetlands with rare and threatened species supported species assemblages, which were different from those without rare or threatened plant species. Rare and threatened species were not associated with rare environments. The presence or richness of rare and threatened species was not associated with wetland size. SLOSS analyses revealed that small wetlands were critical for capturing rare and threatened species and their functional richness. Conclusions Prioritizing wetlands with rare and threatened plant species will not meet other conservation objectives, such as the preservation of all critical community types, rare environments or large wetlands. Networks of small wetlands will be necessary to safeguard rare and threatened plant species. Complementary objectives targeted at wetlands of varying size will be necessary to protect the full range of biodiversity and ecosystem services that wetlands offer.